Pulmonary Helminthosis of Wild Animals of the Trans-Baikal Territory - E. A. Artemyeva; E. V. Kiriltsov (Российский паразитологический журнал, 2019)
The purpose of the research is to study the species diversity of pulmonary helminths of wild animals in the Transbaikal Territory.Materials and methods. The collection of material was carried out in different regions of the Trans-Baikal Territory: Akshinsky, Kirinsky and Krasnochikoysky. In total, 17 elk, 32 Siberian roe deer, and 5 wolves were subjected to helminthological research. The studies were performed by the method of full and partial helminthological autopsy. At autopsy, the intensity and extent of the infection were determined. Faecal samples were studied using the Berman-Orlov method.Results and discussion. The pulmonary helminthosis of wild animals (elk, roe deer, wolf ) of the Transbaikal Territory were studied. Elk revealed the nematodes Dictyocaulus eckerti; the infection extensiveness (IE) was 41%, the infection intensity (II) – 28-76 sp. per head. In Siberian roe deer, nematodes Muellerius capillaris were detected, with IE of 18.7% and II 24-54 sp. per head. Nematodes Crenosoma vulpis (Rudolphi, 1819) were detected in wolves with IE 16.6% and II 38 sp. per head.